2016
DOI: 10.3847/0004-637x/823/1/16
|View full text |Cite
|
Sign up to set email alerts
|

ROTATION PERIODS FOR COOL STARS IN THE 4 Gyr OLD OPEN CLUSTER M67, THE SOLAR–STELLAR CONNECTION, AND THE APPLICABILITY OF GYROCHRONOLOGY TO AT LEAST SOLAR AGE

Abstract: We report rotation periods for 20 cool (FGK) main sequence member stars of the 4 Gyr-old open cluster M 67 (= NGC 2682), obtained by analysing data from Campaign 5 of the K2 mission with the Kepler Space Telescope. The rotation periods delineate a sequence in the color-period diagram (CPD) of increasing period with redder color. This sequence represents a cross-section at the cluster age of the surface P = P (t, M ), suggested in prior work to extend to at least solar age. The current Sun is located marginally… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
131
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(145 citation statements)
references
References 65 publications
11
131
1
2
Order By: Relevance
“…Barnes 2007;Mamajek & Hillenbrand 2008;Barnes & Kim 2010;Angus et al 2015), while others report on stellar data to validate certain gyrochronology relations (e.g. Meibom et al 2011Meibom et al , 2015Barnes et al 2016). Semiphysical spin-down models have also been presented in the literature (van Saders & Pinsonneault 2013;Matt et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Barnes 2007;Mamajek & Hillenbrand 2008;Barnes & Kim 2010;Angus et al 2015), while others report on stellar data to validate certain gyrochronology relations (e.g. Meibom et al 2011Meibom et al , 2015Barnes et al 2016). Semiphysical spin-down models have also been presented in the literature (van Saders & Pinsonneault 2013;Matt et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Gyrochronology can be used to age-date clusters as old as 4 Gyr with a precision of ∼0.7 Gyr (Barnes et al 2016). However, Angus et al (2015) found unexpected deviations from the predicted age versus rotation period relation and they demonstrated that the age uncertainties are significantly higher for field stars.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the enormous progress that has been made in exploring the detailed chemistry of the disk with increasingly larger samples (e.g., LAMOST -Xiang et al 2017;GALAH -De Silva et al 2015;Gaia-ESO -Jacobson et al 2016;Smiljanic et al 2016), field stars nevertheless suffer from various disadvantages that complicate their use in ascertaining the global properties of the disk, including (a) uncertainties in extinction, intrinsic luminosity, and therefore the distances of individual stars, (b) susceptibility to radial migration, which obscures stellar birth locations and presumably blurs disk properties tracked by location, kinematics, metallicity or age, and (c) large systematic and random uncertainties in deriving ages for individual stars (Clem et al 2004;Masana et al 2006) -although there is new promise in resolving this latter problem using the techniques of asteroseismology, gyrochronology (e.g., Angus et al 2015;Barnes et al 2016), and even detailed stellar chemistries for red giant stars (e.g., Ness et al (2016)). …”
mentioning
confidence: 99%
“…Though taken as part of the APOGEE obser-vations of some 146,000 stars in SDSS-III from 2011-2014, the data used in a Estimates for the age of each cluster: NGC 7789's age is taken from Wu et al (2007). M67's age is taken from the average of Schiavon et al (2004), Salaris et al (2004), and Barnes et al (2016). NGC 6819's age is taken from Kalirai et al (2001).…”
mentioning
confidence: 99%